The Analysis of Open Space Configuration as an Evacuation Assembly Point, Case Study: Universitas Bandar Lampung - Kustiani Kustiani; Rendy Perdana Khidmat (JURNAL ARSITEKTUR, 2022)
Apart from functioning as a place for social interaction, open space holds an important role as an emergency evacuation point when a disaster takes place. The concept of open space as an emergency evacuation spot is crucial to be adopted, one of which is in the educational complex, particularly related to the safety of the users such as students, lecturers, staff, etc., and to ensure the social activities among them. This study aims to analyze open space configuration patterns and identify the potential of the open space in the educational area or campus complex, taking as an example, Universitas Bandar Lampung, Lampung (UBL). The research uses a quantitative method that started with data collection from field observation to gather the information about emergency assembly point location settings and conduct space syntax analysis utilizing software called DepthmapX. Furthermore, several analyses, such as Visibility Graph Analysis (VGA), Isovist analysis, and agent tools analysis, have been conducted on the collected data to obtain an image of the UBL open space potential. The result shows that the open space of a car parking area (P3) is the most optimal spot to be the emergency assembly point with the highest values of connectivity, integration, and intelligibility (876.96, 1.08, and 0.23386).